Life history influences rates of climatic niche evolution in flowering plants - Smith, Stephen A. (The Royal Society, 2009)
Across angiosperms, variable rates of molecular substitution are linked with life-history attributes associated with woody and herbaceous growth forms. As the number of generations per unit time is correlated with molecular substitution rates, it is expected that rates of phenotypic evolution would also be influenced by differences in generation times. Here, we make the first broad-scale comparison of growth-form-dependent rates of niche evolution. We examined the climatic niches of species on large time-calibrated phylogenies of five angiosperm clades and found that woody lineages have accumulated fewer changes per million years in climatic niche space than related herbaceous lineages. Also, climate space explored by woody lineages is consistently smaller than sister lineages composed mainly of herbaceous taxa. This pattern is probably linked to differences in the rate of climatic niche evolution. These results have implications for niche conservatism; in particular, the role of niche conservatism in the distribution of plant biodiversity. The consistent differences in the rate of climatic niche evolution also emphasize the need to incorporate models of phenotypic evolution that allow for rate heterogeneity when examining large datasets.